Impact of Different Soil Management Practices and Fertilizer Combinations on Yield and Quality of Chicken Pea (Cicer arietinum L.) - Ahmadreza Farshchian; Zahra Talebpour; Sima Najafi; Narmin Najafzadeh (Politeknik Negeri Jember, 2023)
Soil cultivation practices and fertilizer managements significantly influence crop performance and yield. Our study aimed to evaluate the impact of different soil management techniques and the integration of organic and chemical fertilizers on the quantitative and qualitative performance of chicken peas (Cicer arietinum L.). Our results revealed that soil management and fertilizer sources had a significant impact on the number of pods per plant and seed yield. The highest number of pods per plant was observed in the conservation tillage treatment with 50% nitrogen fertilizer and mycorrhizal inoculation. The number of seeds per pod was influenced by fertilizer sources, with the highest number obtained in the treatment without soil amendment, 100% nitrogen fertilizer, and no mycorrhizal inoculation. Grain yield was highest in the conservation tillage treatment with 50% nitrogen fertilizer and mycorrhizal inoculation. The results highlighted that optimal nitrogen fertilizer integrated with mycorrhizal improves nutrient uptake and increases yield components. This study highlights the importance of fertilizer and soil management in optimizing chicken pea performance. The positive effects of balanced nitrogen fertilizer integrated with mycorrhizal inoculation were recorded on yield-related traits. These findings contribute to the development of sustainable agricultural practices that reduce reliance on chemical fertilizers and enhance crop productivity.